Edukasi Hukum Hak Asasi Manusia dalam KUHAP Baru Bagi Masyarakat Kota Bima - Andriadin; Ilham; Kasmar (SEWAGATI: Jurnal Pengabdian kepada Masyarakat, 2026)
The enactment of Law Number 20 of 2025 on the Criminal Procedure Code (KUHAP), effective January 2, 2026, marks a paradigm shift in Indonesia’s criminal justice system toward a due process of law approach emphasizing human rights protection. However, public legal literacy, particularly in peripheral areas such as Bima City, has not kept pace with these reforms. This community service initiative aimed to improve public understanding of new KUHAP while fostering dialogue among academics, law enforcement officials, and the community. Methods included participatory legal outreach, group discussions, case simulations, and pre-and post-test evaluations involving 112 participants. Findings showed improved understanding of expanded pretrial proceedings, suspect designation criteria, the right to legal counsel, and restorative justice, although procedural comprehension requires enhancement. Sustainable legal literacy programs through collaboration among universities, local governments, and law enforcement agencies, supported by context-specific educational modules, are recommended to promote effective implementation and strengthen human rights protection.